Frontier Technology Readiness, Democracy, and Income Inequality in Africa - Isaac K. Ofori (ZBW - Leibniz Information Centre for Economics, 2024)
The proliferation of frontier technologies in the Global South has increased over the past decade. Despite this development, rigorous empirical findings regarding their socioeconomic impacts within the context of Africa are hard to find. This study addresses this gap by employing macro data from 39 African countries to investigate the impact of frontier technology adoption (FTR) on income inequality. Additionally, the study explores whether democracy serves as a moderator of FTR, influencing a more equitable income distribution. Furthermore, this study assesses the inequality impacts of FTR across various policy thresholds of democracy. Results from the dynamic system GMM estimator reveal that: (i) FTR increases income inequality, (ii) democracy, particularly electoral and participatory democracy, mitigates income inequality, and (iii) FTR reduces income inequality only at a higher threshold of democracy (0.5 or better). This leads to the conclusion that, without inclusive democracy, FTR may impede Africa's social progress agenda by widening the income disparity gap.
Keywords: I3; O31; O33; Q55; Q01; 330; Africa; Frontier Technology Readiness; Democracy; Income Inequality